Pan-Filovirus Serum Neutralizing Antibodies in a Subset of Congolese Ebolavirus Infection Survivors. (13th August 2018) - Bramble, Matthew S; Hoff, Nicole; Gilchuk, Pavlo; Mukadi, Patrick; Lu, Kai; Doshi, Reena H; Steffen, Imke; Nicholson, Bradly P; Lipson, Allen; Vashist, Neerja; Sinai, Cyrus; Spencer, D'andre; et al.
Abstract : Infection with Zaire ebolavirus (EBOV) appears to trigger an anti–pan-filovirus response in a small subset of Congolese Ebola virus disease survivors, generating potential neutralizing antibodies against EBOV and Bundibugyo, Taï Forest, Sudan, and Marburg viruses. Abstract: One year after a Zaire ebolavirus (EBOV) outbreak occurred in the Boende Health Zone of the Democratic Republic of the Congo during 2014, we sought to determine the breadth of immune response against diverse filoviruses including EBOV, Bundibugyo (BDBV), Sudan (SUDV), and Marburg (MARV) viruses. After assessing the 15 survivors, 5 individuals demonstrated some degree of reactivity to multiple ebolavirus species and, in some instances, Marburg virus. All 5 of these survivors had immunoreactivity to EBOV glycoprotein (GP) and EBOV VP40, and 4 had reactivity to EBOV nucleoprotein (NP). Three of these survivors showed serologic responses to the 3 species of ebolavirus GPs tested (EBOV, BDBV, SUDV). All 5 samples also exhibited ability to neutralize EBOV using live virus, in a plaque reduction neutralization test. Remarkably, 3 of these EBOV survivors had plasma antibody responses to MARV GP. In pseudovirus neutralization assays, serum antibodies from a subset of these survivors also neutralized EBOV, BDBV, SUDV, and Taï Forest virus as well as MARV. Collectively, these findings suggest that some survivors of naturally acquired ebolavirus infection mount not only a pan-ebolavirus response, but also in less frequent cases, a pan-filovirus neutralizing response.